Exposure to short-, medium-, and long-chain chlorinated paraffins for infant via cow infant formula, goat infant formula and baby food. (July 2022) - Luo, Yadan; Li, Juan; Gao, Wei; Gao, Lirong; Ke, Runhui; Yang, Chunyan; Wang, Yingjun; Gao, Yan; Wang, Yawei; Jiang, Guibin
Abstract: Dietary exposure is an important pathway for many pollutants from external exposure to human beings. In this study, we investigated the exposure to short-chain chlorinated paraffins (SCCPs), medium-chain chlorinated paraffins (MCCPs) and long-chain chlorinated paraffins (LCCPs), which are a class of industrial compounds that are of significant concern, in different infant foods (cow infant formula, goat infant formula and baby food are collectively called infant food in this study) in Chinese market. The concentrations of ∑SCCPs, ∑MCCPs and ∑LCCPs in infant foods were in the ranges of 6.22–273 ng/g, 13.1–2020 ng/g and 0.80–1280 ng/g, respectively. Especially, for the first time, we found that the proportion of ∑LCCPs (22.0%) in goat infant formula is almost equivalent to that of ∑SCCPs (25.0%), implying that LCCPs should also be further concerned since the related information is very scarce. There were differences between CP profiles among imported cow infant formula and Chinese cow infant formula due to the different sources of CPs to the infant formula. Imported infant foods were characterized by higher proportion of SCCPs, while Chinese infant foods were characterized by higher proportion on LCCPs. Margin of exposure results demonstrated that there was no significant health concern for the infant, but that large variation of CP concentrations and excessive feeding in practice may cause potential health threats to the infant. LCCPs were detected in all infant food samples, and to our knowledge, this is the first report of LCCPs in cow infant formula, goat infant formula and baby food. This study could provide important data of infant exposure to CPs, especially, LCCPs. Graphical abstract: Image 1 Highlights: Exposure to SCCPs, MCCPs and LCCPs were estimated via Chinese cow infant formula, goat infant formula, baby food and imported cow infant formula. Margin of exposure results demonstrated that there was no significant health concern for the infant. The proportion of ∑LCCPs in goat infant formula is almost equivalent to the proportion of ∑SCCPs. LCCPs were detected in all samples, to our knowledge, this is the first report to compare LCCPs in cow infant formula, goat infant formula and baby food.